The effects of yoga on breast-cancer-related lymphedema: a systematic review - Ausanee Wanchai; Jane M. Armer (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - Breast-cancer-related lymphedema (BCRL) is a negative condition that affects biopsychosocial aspects of patients treated with breast cancer. Yoga has been reported as one of the complementary and alternative approaches used by patients diagnosed with BCRL. The aim of this systematic review was to explore the effectiveness of yoga on BCRL. Design/methodology/approach - A systematic literature was performed by searching existing papers from the electronic scientific databases. Five papers were exclusively examined. Four studies were conducted in women with BCRL, and one study was conducted with women at risk for BCRL. Findings - Four types of yoga were evaluated in relationship with BCRL, namely: the Satyananda Yoga tradition, the modified Hatha yoga, the aerobic yoga training and the Ashtanga-based yoga practices. Four of five included studies reported that decrease in arm volume was not reported for all yoga-type interventions. One study showed no significant evidence that yoga was associated with limb volume change in women at risk of BCRL. Similarly, three studies reported that the change-of-arm-volume measures were not significantly different between the yoga and the control groups or in the same group before and after the yoga program. One quasi-experimental study reported arm volume significantly decreased after attending the yoga program. Originality/value - This review reported the importance of being aware that yoga is not shown to be an effective strategy for managing or preventing BCRL. However, quality of research methodology, small sample sizes and the limited number of related studies should be acknowledged. Until more rigorous studies are performed, yoga may continue to be used as a complement to traditional therapy under the supervision of certified trainers.